Community-led organisations’ impact on health and well-being in disadvantaged areas in the UK: evidence from the CommonHealth Assets longitudinal study - Sarkis Manoukian; Rachel Mairi Baker; Nicola Irvine; Jack Rendall; Helen Mason; Artur Steiner; Marcello Bertotti; Jill Mulholland; Karen Galway; Michael P Kelly (Journal of Epidemiology and Community Health, 2026)
Background Community-led organisations (CLOs) are place-based, community governed entities that aim to enhance health and well-being in disadvantaged communities using asset-based approaches. Currently the relationship between CLO participation and health and well-being outcomes is unclear. Methods A prospective, longitudinal survey was designed as part of a multimethod, realist study: CommonHealth Assets. Questionnaires at baseline, 1, 6 and 12 months assessed capability, health-related quality of life (HR-QoL), mental well-being, social connectedness and CLO attendance patterns (n=316 adults, 14 UK CLOs). Multilevel mixed-effects models assessed associations between participation and well-being outcomes, adjusting for participant and CLO characteristics. Results Higher total CLO engagement was positively associated with mental well-being (Coeff: 0.895, 95% CI 0.178 to 1.612, p=0.015) and capability well-being (Coeff: 0.025, 95% CI −0.003 to 0.053, p=0.081). Child and family activities showed positive associations with capability well-being (Coeff: 0.087, 95% CI 0.035 to 0.138, p=0.001) and social connectedness (Coeff: 0.357, 95% CI 0.117 to 0.597, p=0.004). Frequency analysis revealed linear dose–response relationships for outdoor activities on HR-QoL (Coeff: 0.113, 95% CI 0.037 to 0.189, p=0.004) and non-linear relationships for others such as volunteering on capability well-being (linear Coeff: 0.101, p=0.023; squared Coeff: −0.057, p=0.041) and educational activities on HR-QoL (squared Coeff: 0.308, 95% CI 0.122 to 0.495, p=0.001). Conclusion CLO engagement is associated with better well-being outcomes. Associations vary by activity, revealing temporal and dose–response patterns. Findings provide robust quantitative evidence consistent with the premise that CLOs can enhance different dimensions of well-being, informing intervention design, resource allocation and policy.